Active properties of edible marine polysaccharide-based coatings containing Larrea nitida polyphenols enriched extract. (May 2020) - Moreno, María Alejandra; Bojorges, Hylenne; Falcó, Irene; Sánchez, Gloria; López-Carballo, Gracia; López-Rubio, Amparo; Zampini, Iris Catiana; Isla, María Inés; Fabra, María José
Abstract: The aim of this work was to develop active edible coatings based on marine polysaccharide matrices and polyphenols-enriched native plant extracts from arid and semiarid regions of Argentina. Initially, five plant extracts were characterized in terms of antioxidant, antibacterial and antiviral activity and the one with better biological properties and no toxicity or genotoxicity, Larrea nitida (Ln) extract, was incorporated into agar, alginate or agar/alginate matrices. The Ln extract-containing films were characterized in terms of physicochemical and polyphenols release performance in food simulants. The incorporation of Ln extract provided darker films, with a more saturated orange-brownish color and with negligible effects on mechanical and barrier properties. Additionally, all the coatings showed antiviral activity when applied to blueberries against murine norovirus (MNV), a cultivable norovirus surrogate. The coatings of agar and Ln extract was able to reduce the infectivity of MNV below the limit of detection after over-night (ON) incubation at 25 °C and after 4 days at 10 °C storage. These edible polysaccharides coatings containing Ln extract could be an alternative to reduce or eliminate foodborne viruses and protect the food against oxidative process. Graphical abstract: Image 1 Highlights: Polyphenolic plant extracts were used for the development of active edible coatings. Larrea nitida extract showed the greatest antioxidant and antimicrobial properties. Ln extract was not toxic or genotoxic at the concentration used (500 μg/mL). Antioxidant and antimicrobial coatings were formed with agar, alginate and Ln extract. Ln containing coatings reduced the titers of MNV in artificially contaminated berries.